2009
DOI: 10.2169/internalmedicine.48.2181
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil-Induced Adverse Side Effects of Cardiac Rhythm: 2 Cases Report of Atrioventricular Block and Torsade de Pointes

Abstract: Acetylcholinesterase inhibitors (AChIs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…However, none of these studies gave detailed information on the adverse effects of donepezil on the cardiac conduction system, such as QT prolongation (19)(20)(21)(22)(23)(24). Moreover, it was also reported that bradycardia, complete atrioventricular block and QT prolongation were seen in patients taking donepezil (24)(25)(26)(27)(28). Therefore, there has been significant anxiety among prescribers regarding the potential for cardiac adverse effects associated with ChEIs, such as donepezil in elderly patients with AD (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies gave detailed information on the adverse effects of donepezil on the cardiac conduction system, such as QT prolongation (19)(20)(21)(22)(23)(24). Moreover, it was also reported that bradycardia, complete atrioventricular block and QT prolongation were seen in patients taking donepezil (24)(25)(26)(27)(28). Therefore, there has been significant anxiety among prescribers regarding the potential for cardiac adverse effects associated with ChEIs, such as donepezil in elderly patients with AD (29).…”
Section: Discussionmentioning
confidence: 99%
“…This drug is effective and well tolerated with less adverse effects than other inhibitors of acetylcholinesterase, such as physostigmine and tacrine (Sugimoto et al, 2000). However, several case reports have stated that donepezil induces adverse side effects of cardiac rhythm, such as prolonged QT interval and Torsade de Pointes arrhythmias (Takaya et al, 2009;Tanaka et al, 2009). One of the mechanisms of QT prolongation and Torsade de Pointes includes the blockage of the human ethera-go-go-related gene (hERG) current, which underlies the rapidly activating delayed rectifier voltage-gated K þ (Kv) currents in human cardiomyocytes (Thomas et al, 2002;Witchel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focused on the interaction of donepezil and cilostazol at efflux transporters as a potential explanation of the clinically reported cardiotoxicity of donepezil when coadministered with cilostazol (Tanaka et al, 2009;Shinozaki, 2012;Igeta et al, 2013). This is an important issue because simultaneous use of donepezil and cilostazol has been proposed to improve the pharmacologic outcome (Lee et al, 2007;Ihara et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that donepezil may cause cardiac toxicity, such as QT prolongation (Takaya et al, 2009). There are also case reports of cardiac toxicity of donepezil in patients concurrently receiving cilostazol, benidipine, or memantine (Tanaka et al, 2009;Shinozaki, 2012;Igeta et al, 2013). However, the mechanism of the putative drug-drug interaction (DDI) has not yet been clarified, even though donepezil is often administered with other drugs, as it is frequently prescribed for elderly people.…”
Section: Introductionmentioning
confidence: 99%